A Bait-and-Switch Model of Corporate Social Responsibility - Haack, Patrick; Martignoni, Dirk; Schoeneborn, Dennis (Academy of Management Review, 2021)
The notion that transparency forces organizations to eschew decoupling and embrace substantive adoption represents an important assumption in the corporate social responsibility (CSR) literature. Conversely, research on learning and social control has considered opacity—understood as a lack of transparency—to be conducive to substantive CSR adoption. These opposing viewpoints highlight a fundamental tension: Is transparency good or bad for substantive adoption? This paper resolves this tension by asking an alternative question: When is transparency good or bad, and why? We advance a dynamic perspective that conceives transparency and opacity as transitory phenomena, and we specify the boundary conditions for which either enduring or transitory forms of transparency and opacity further the substantive adoption of CSR. Our analyses reveal that, for circumstances under which the motivation of ceremonial adoption is hypocritical (rather than opportunistic) and where both substantive adoption and practice abandonment are difficult, the former can be maximized by first allowing organizations to adopt a CSR practice ceremonially under opacity (“bait”), and then prompting ceremonial adopters to become substantive adopters through a shift to transparency (“switch”). Specifying this bait-and-switch mechanism and its underlying contingencies reveals a hitherto unexplored, and potentially effective, pathway toward the institutionalization of CSR.